The effects of online learning on English language education during the COVID-19 pandemic: A meta-analysis - Ratna Yunita (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to conclude the effects of online learning on English language education during the coronavirus disease (COVID-19) pandemic. This meta-analysis study examined the results of relevant studies conducted and published in variouscountries worldwide within the two years of the pandemic (between January 2020 to April 2022). With a database of 430 research, only eight articles met the inclusion requirements to answer the overview of the effects and four articles to answer the overall effect, benefits, and drawbacks of online learning on English language education. The data were analysed quantitatively and qualitatively. Data in percentages and figures representing the effects of online learning were analysed using quantitative methods. The important research findings, including the advantages and disadvantages of online learning based on content analysis, were described using qualitative data analysis. The objectives of researching online learning in English language education, forms of online learning research, samples, analyses of online learning research data, and settings of online learning research were discovered from the eight research publications this meta-analysis found. The outcomes demonstrated that online learning positively impacted English language instruction during the COVID-19 pandemic.